Avaliação da capacidade de adsorção do CO2 em zeólita 12X com gases sintéticos e originados da pirólise do lodo de esgoto - Lessa, Mayara de Oliveira (2012)
This work depicts a study of the adsorption of carbon dioxide on zeolite 13X. The activities were divided into four stages: study batch adsorption capacity of the adsorbent with synthetic CO2 (4%), fixed bed dynamic evaluation with the commercial mixture of gases (4% CO2, 1.11% CO, 1 2% H2, 0.233% CH4, 0.1% C3, 0.0233% C4 argon as inert closing balance), fixed bed dynamic modeling and evaluation of the breakthrough curve of CO2 originated from the pyrolysis of sewage sludge. The sewage sludge and the adsorbent were characterized by analysis TG / DTA, SEM, XRF and BET. Adsorption studies were carried out under the following operating conditions: temperature 40 °C (for the pyrolysis of the sludge T = 600 °C), pressures of 0.55 to 5.05 bar (batch process), flow rate of the gaseous mixture between 50 - 72 ml/min and the adsorbent masses of 10, 15 and 20 g (fixed bed process). The time for the adsorption batch was 7 h and on the fixed bed was around 180 min. The results of this study showed that in batch adsorption process step with zeolite 13X is efficient and the mass of adsorbed CO2 increases with the increases pressure, decreases with temperature increases and rises due the increase of activation temperature adsorbent. In the batch process were evaluated the breakthrough curves, which were compared with adsorption isotherms represented by the models of Langmuir, Freündlich and Toth. All models well adjusted to the experimental points, but the Langmuir model was chosen in view of its use in the dynamic model does not have implications for adsorption (indeterminacy and larger number of parameters such as occurred with others) in solving the equation. In the fixed bed dynamic study with the synthetic gas mixture, 20 g of mass adsorbent showed the maximum adsorption percentage 46.7% at 40 °C temperature and 50 mL/min of flow rate. The model was satisfactorily fitted to the three breakthrough curves and the parameters were: axial dispersion coefficient (0.0165 dm2/min), effective diffusivity inside the particle (dm2/min 0.0884) and external transfer coefficient mass (0.45 dm/min). The breakthrough curve for CO2 in the process of pyrolysis of the sludge showed a fast saturation with traces of aerosols presents in the gas phase into the fixed bed under the reaction process